LOVE AFFAIR REFLECTED AT HENRIK IBSEN’S HEDDA GABLER PLAY (1890); AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Maya Berlian Primadani; Dewi Candraningrum; Titis Setyabudi (Universitas Muhammadiyah Surakarta, 2014)
The present study investigates love affair in Henrik Ibsen’s Hedda Gabler. This was library research of which primary data source was Hedda Gabler play supported by other resources such as the author’s biography. The data were analyzed based on the individual psychology with a descriptive technique. The result showed that love affair was conducted by the major character, Hedda.